Tradisi Sayyang Pattu'du di Mandar (Studi Kasus Desa Lapeo) - Ruhiyat Ruhiyat (LP2M IAIN Palangka Raya, 2017)
In the sociological view, Mandarese believes that Sayyang Pattu‟du‟ tradition has a close affinity with each other. As a reason, Pattu'du‟ Sayyang tradition was held in order to appreciate the children who have finished readying all the content of their Al-Qur‟an. For the resident of Mandar especially in Lapeo village, the Tradition of Sayyang Pattu'du‟ meant as a socialization tool because involve the resident in an effort to achieve a goal together. In addition, this tradition can also increase the integration and strengthen the solidarity process among the resident. It was unquestionable if in the midst of this tradition‟s process some of the various groups of people take advantages from this moment on their behalf. Therefore, the problems appears in this research are how the image of the interaction and social dynamic within the tradition of Sayyang Pattu'du‟ and to what extent the resident of Lapeo village interpret Sayyang Pattu'du’ tradition.